Effectiveness of Childpose (Balasana) Exercise as a Complementary Therapy to Reduce Back Pain in Third Trimester Pregnant Women at the South Bolango Community Health Center - Nurul Riza Armita; Anik Purwati (Green Health International Journal of Health Sciences Nursing and Nutrition, 2025)
In order to guarantee the best possible maternal health and fetal growth throughout pregnancy, complementary services for expectant mothers are required. These services include nutrition, mental health, and supplementary medical treatment. According to data, 70% of pregnant women have low back discomfort. According to a different poll, eight out of ten third-trimester pregnant women report having back pain. Doing Childpose (Balasana) exercises is one more way to lessen this problem. This study sought to ascertain if Childpose (Balasana) exercises were beneficial in lowering low back pain complaints among pregnant women in their third trimester at the South Bolango City Health Center. This study employed a quasi-experimental pretest-posttest approach with a sample of 34 pregnant women in the third trimester. There were twenty participants in the study's sample. Childpose or balasana exercises are beneficial in relieving back discomfort in third trimester pregnant women at the South Bolango Health Center, according to the data, which indicated a P-value of 0.000 <0.05.